Endolymphatic duct blockage: a randomized controlled trial of a novel surgical technique for Ménière's disease treatment - Saliba, Issam; Gabra, Nathalie; Alzahrani, Musaed; Berbiche, Djamal (Otolaryngology-head and neck surgery, 2015)
To compare the effectiveness of the endolymphatic duct blockage (EDB) and the endolymphatic sac decompression (ESD) to control Ménière's disease symptoms and to evaluate their effect on hearing level. Prospective nonblinded randomized study. Tertiary medical center. Fifty-seven patients affected by a refractory Ménière's disease were included out of which 22 underwent an ESD and 35 underwent an EDB. Five periods of follow-up were considered: 0 to 1 week, 1 week to 6 months, 6 to 12 months, 12 to 18 months, and 18 to 24 months. Mean outcome measurements consisted of vertigo control, tinnitus, aural fullness, instability, and hearing level. Hearing level was evaluated using pure-tone average (PTA) and speech discrimination score (SDS). There was no significant difference between the 2 groups in the number of vertigo spells per months preoperatively (P = .153). Twenty-four months postoperatively, 96.5% of the EDB group had achieved a complete control of vertigo spells against 37.5% of the ESD group with a statistically significant difference (P = .002). There was a better control of tinnitus and aural fullness with EDB (P = .021 and P = .014, respectively). There was no statistically significant difference in hearing level preoperatively (P = .976) and 24 months postoperatively (P = .287) between the 2 groups. Hearing level was preserved in each group with no significant difference between the preoperative and the postoperative levels (P > .05). EDB is more effective than the traditional ESD in controlling the symptoms of Ménière's disease. It is a novel surgical technique with promising results for a complete treatment of Ménière's disease. There are no significant complications or adverse effect.